An empirical exploration of the role of strategic and responsive corporate social responsibility in the adoption of different Green IT strategies. (20th May 2016) - Bohas, Amélie; Poussing, Nicolas
Abstract: There are few studies of the impact of firms' voluntary measures in terms of the determinants of environmental change. This paper aims to address this gap by examining the role played by corporate social responsibility in the adoption of Green IT. We consider two different corporate social responsibility policies and different typologies of Green IT. We believe that corporate social responsibility (CSR) plays a role in the adoption of Green IT and different CSR strategies induce the implementation of different types of Green IT in the firms. We utilise a survey carried out in Luxembourg on firms' CSR practices together with a community survey on information and communication technology usage by enterprises. Our estimations show that corporate social responsibility is a driver of Green IT adoption. We also show that strategic and responsive CSR induce the adoption of different types of Green IT based on the intensity of changes but all CSR strategies have the same effect on Green IT typology based on the moment when Green IT is adopted. Highlights: We improve the understanding of the relationship between CSR and Green IT. We test this relationship using data at firm level. We contribute toPorter and Kramer's (2006) strategic CSR model. We show the importance of taking into account different CSR strategies and Green IT policies.